METODE CERITA ISLAMI DALAM PENGEMBANGAN KOGNITIF ANAK USIA DINI TAMAN KANAK-KANAK MARDI PENI 2 DEMAK - Sofiatun Sofiatun (An-Nida : Jurnal Komunikasi Islam, 2022)
The objectives of this study are: 1) to describe the implementation of the Islamic story method in early childhood cognitive development in Mardi Peni 2  Karanganyar Kindergarten, Demak Regency. 2) describe the results of the implementation of the Islamic story method in early childhood cognitive development at Mardi Peni 2 Karanganyar Kindergarten, Demak Regency. This research is a qualitative descriptive study. Collecting data using observation, interviews and documentation. This study uses inductive data analysis. The data analysis process in this study took several stages, namely: data collection, codification and categorization. The results showed that the application of the Islamic storytelling method to develop children's cognitive was done by preparing teaching materials and telling stories to students with teacher improvisation so that learning became interesting and students felt happy listening to stories. Islamic stories that are often read to students are stories of the prophet, the struggles of Muslims, and advice in the Qur'an. The results of the implementation of the Islamic storytelling method are very helpful for students' cognitive development, starting from the sensory-motor stage, pre-operational stage, and concrete operational stage.